2020
DOI: 10.3390/en13102596
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Optimal Energy Management Strategies for Energy Storage with Stochastic Loads

Abstract: This paper aims to present the significance of predicting stochastic loads to improve the performance of a low voltage (LV) network with an energy storage system (ESS) by employing several optimal energy controllers. Considering the highly stochastic behaviour that rubber tyre gantry (RTG) cranes demand, this study develops and compares optimal energy controllers based on a model predictive controller (MPC) with a rolling point forecast model and a stochastic model predictive controller (SMPC) based on a stoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Without these investigations and comparisons, it is difficult to assess the value or importance of the forecast's quality. A few examples, including [199], [8] have shown that improved forecast accuracy can improve the performance of the application. Further [125] shows that using prediction intervals improves peak load reduction compared to some basic point forecast methods.…”
Section: Discussionmentioning
confidence: 99%
“…Without these investigations and comparisons, it is difficult to assess the value or importance of the forecast's quality. A few examples, including [199], [8] have shown that improved forecast accuracy can improve the performance of the application. Further [125] shows that using prediction intervals improves peak load reduction compared to some basic point forecast methods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this work aims to develop and present an optimal energy controller for the ESS to improve the power network performance compared to the common energy controller, the set-point algorithm [25]. The optimal energy controller aims to find the optimal ESS operation condition (charging and discharging).…”
Section: The Description Of the 100% Pv And Ess Systems And Methodologymentioning
confidence: 99%
“…The main components of the proposed system in this paper, as presented in Figure 2, will be discussed in the following subsections. In addition, this work aims to develop and present an optimal energy contro the ESS to improve the power network performance compared to the common controller, the set-point algorithm [25]. The optimal energy controller aims to find timal ESS operation condition (charging and discharging).…”
Section: The Description Of the 100% Pv And Ess Systems And Methodologymentioning
confidence: 99%
See 2 more Smart Citations